Karakteristik Rumah Tinggal Konstruksi Hibrida (Hybrid) Masyarakat Suku Kaili di Kabupaten Sigi - Muhammad Dwi Utomo; Zulfitriah Masiming (Fakultas Teknik Universitas Cenderawasih, 2026)
Indonesia, as a country located at the intersection of three tectonic plates, is highly vulnerable to earthquakes. This has led to the development of various innovations in earthquake-resistant housing. An interesting phenomenon can be found in Sigi District, Central Sulawesi, where several vernacular houses of the Kaili people constructed with a hybrid design (wooden frame and mud walls) have proven to withstand the major earthquake that struck Palu, Central Sulawesi, in 2018. This study aims to examine the architectural typology of non-engineered hybrid houses within the Kaili community using a qualitative descriptive approach and typological analysis. Data collection involved direct observation, interviews, and literature reviews, with a focus on the spatial and physical systems of the buildings. The sample for the study was determined through purposive sampling with specific criteria. Data analysis was conducted using a qualitative descriptive approach. The results of the study indicate that, despite changes in materials due to adaptations to technological advancements and reconstruction policies, the spatial layout and fundamental structure of the houses have maintained traditional philosophies. These houses demonstrate the integration of cultural values, local knowledge about seismic activity, and the use of local materials, which allow for both structural flexibility and some rigidity, contributing to the buildings’ resilience. These findings highlight the importance of combining technical and cultural approaches in designing earthquake-resistant houses within a local context.